Regulation of Transcription at the Saccharomyces cerevisiae Start Transition by Stb1, a Swi6-Binding Protein - Ho, Yuen (American Society for Microbiology, 1999)
In Saccharomyces cerevisiae, gene expression in the late G(1) phase is activated by two transcription factors, SBF and MBF. SBF contains the Swi4 and Swi6 proteins and activates the transcription of G(1) cyclin genes, cell wall biosynthesis genes, and the HO gene. MBF is composed of Mbp1 and Swi6 and activates the transcription of genes required for DNA synthesis. Mbp1 and Swi4 are the DNA binding subunits for MBF and SBF, while the common subunit, Swi6, is presumed to play a regulatory role in both complexes. We show that Stb1, a protein first identified in a two-hybrid screen with the transcriptional repressor Sin3, binds Swi6 in vitro. The STB1 transcript was cell cycle periodic and peaked in late G(1) phase. In vivo accumulation of Stb1 phosphoforms was dependent on CLN1, CLN2, and CLN3, which encode G(1)-specific cyclins for the cyclin-dependent kinase Cdc28, and Stb1 was phosphorylated by Cln-Cdc28 kinases in vitro. Deletion of STB1 caused an exacerbated delay in G(1) progression and the onset of Start transcription in a cln3Δ strain. Our results suggest a role for STB1 in controlling the timing of Start transcription that is revealed in the absence of the G(1) regulator CLN3, and they implicate Stb1 as an in vivo target of G(1)-specific cyclin-dependent kinases.